Gentala Arasy Jambi Museum Promotion Strategy in Increasing Tourist Visits - Sukmamedian, Haufi; Superwiratni; Permatasari, Mustika (Journal of Business and Management Inaba, 2024)
The large amount of tourist interest has not been supported by adequate facilities. One of them is access to the Gentala Arasy museum through the bridge, there are so many old street vendors who sell without rules so that it seems shabby, the lack of maintenance of lights on the Gentala Arasy bridge and at the Gentala Arasy Museum also affects the attractiveness of the tourist attraction that is the icon of Jambi City. Based on this presentation, we can see that the Gentala Arasy Museum is an interesting tourist attraction to visit, and good management is needed so that tourists who come are amazed and get a good memory of the Gentala Arasy Museum. The collected data is recorded and processed using a computer. The results will be presented in table form and then analyzed quantitatively descriptively. The known formula to determine the level of respondents' conformity between expectations and reality. 5 dimensions of characteristics used by customers in evaluating service quality, namely: reliability, responsiveness, assurance, empathy, tangible.